2019
DOI: 10.3390/cells8040298
|View full text |Cite
|
Sign up to set email alerts
|

miR-1306 Mediates the Feedback Regulation of the TGF-β/SMAD Signaling Pathway in Granulosa Cells

Abstract: Transforming growth factor-β receptor II (TGFBR2), the type II receptor of the TGF-β/SMA- and MAD-related protein (SMAD) signaling pathway, plays a crucial role in TGF-β signal transduction and is regulated by multiple factors. Nevertheless, the modulation of the non-coding RNA involved in the process of TGFBR2 expression in ovaries is not well studied. In our study, we isolated and characterized the 3′-untranslated region (UTR) of the porcine TGFBR2 gene and microRNA-1306 (miR-1306) was identified as the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
0
28
2
Order By: Relevance
“…Furthermore, FACS revealed that FZD4 depletion significantly induced GC apoptosis ( Fig. 1h), indicating that FZD4, like its inducer SMAD4, is an antiapoptotic factor in porcine GCs 41 .…”
Section: Smad4 Is a Strong Inducer Of Fzd4 In Porcine Gcsmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, FACS revealed that FZD4 depletion significantly induced GC apoptosis ( Fig. 1h), indicating that FZD4, like its inducer SMAD4, is an antiapoptotic factor in porcine GCs 41 .…”
Section: Smad4 Is a Strong Inducer Of Fzd4 In Porcine Gcsmentioning
confidence: 90%
“…After incubation on ice for 30 min, the supernatant was collected by 12,000 × g centrifugation for 15 min at 4°C. The BCA Protein Assay Kit (#P0012, Beyotime, Jiangsu, China) was used to detect the concentration of total protein and western blotting was conducted as described previously 41 . Primary antibodies were anti-FZD4 (Sangon Biotech, #D121422, 1:1000), anti-β-catenin (Sangon Biotech, #D260137, 1:1000), anti-caspase-3/ cleaved caspase-3 (Proteintech, #19677-1-AP, 1:1000), and anti-GAPDH (ORIGENE, #TA802519, 1:5000).…”
Section: Western Blottingmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that miRNAs are important endogenous regulators of gene expression, which have been investigated in various biological mechanisms [ 24 , 39 41 ]. However, with the increasing amounts of discovered lncRNAs, the function of very few lncRNAs has been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…While miR-1306 is encoded in most eukaryotic species, miR-3618 is restricted to primates (Merico et al, 2014). MiR-1306 targets F-box/Leucine rich repeat 5 (FBLX5), affecting epithelial to mesenchymal transitions and TGF beta-receptor 2, which is involved in the TGF-beta-SMAD4 signaling process ( Figure 2) (He et al, 2018;Yang et al, 2019). Other haploinsufficient miRNAs include miR-1286, selectively encoded in advanced primates, with in situ hybridization revealing its expression in the occipital cortex (Nowakowski et al, 2018).…”
Section: Digeorge Syndrome Critical Region 8 and Microrna Contributiomentioning
confidence: 99%